Analisis Pengaruh Barang Substitusi dan Komplementer terhadap Fungsi Permintaan Cabai di Indonesia - Alif Haidir Adana; Lorenta In Haryanto; Nurul Fitriah; Inatsa Thurfah Soerinda (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The demand for red chilies grows yearly, in tandem with the increase in population or industries that use red chili as raw resources. This research aims to examine the effect of the determiner of chili demand in Indonesia and categorize them as substitutes or complementary goods. This research employs a quantitative descriptive design with secondary data analysis from the Central Bureau of Statistics. The variables studied were the average prices of red chilies, cayennes pepper, tomatoes, shallots, and garlic in Indonesia from 2010 to 2020. Cayenne pepper, tomato, garlic, and garlic prices significantly affect the 1% level, whereas the population does not affect red chili demand. The analytical tool used is the Cobb-Douglas model regression and elasticity analysis. The result shows that the impact of cayenne pepper, tomato, and garlic prices is directly proportional to the demand for red chilies. On the other hand, shallots significantly have an inverse impact on the demand for chilies. The high price of cayenne pepper, the cost of tomatoes, also the price of garlic will increase the demand for red chili, while the high price of shallots will reduce the need for red chili. According to price elasticity analysis, the cost of red chili is elastic to the demand for red chili in Indonesia. Cross-elasticity analysis shows that cayennes pepper, tomatoes, and garlic are substitutes, while shallots are complementary goods to red chilies.